Herbs issue with knowledge, attitudes, and behavior Bangunjiwo Cadres in Bantul - Indrayanti, Indrayanti; Hidayati, Titiek; Haris, Tauranaswa Farrelabhista Putra; Pradhana, Muhammad Ilham Satya; Amal, Muhammad Ikhlasul (Institute of Computer Science (IOCS), 2025)
The use of herbs as part of traditional health efforts is still widely in demand by the community, so the role of health cadres is needed in providing appropriate education. This study aims to analyze the effect of training on the knowledge, attitudes, and behavior of health cadres at Kasihan I Health Center regarding the use of herbs. The research method used was quantitative with a pre-experimental one group pretest-posttest design. The results of the analysis showed that training had a positive effect on increasing knowledge and changing the behavior of cadres in the use and counseling of herbs. Training had a significant effect on the attitudes (p = 0.00) and behavior (p = 0.002) of health cadres about herbs. However, the effect on attitudes was not statistically significant. These findings indicate the importance of strengthening the affective aspect in training programs so that changes in attitudes occur in line with increased knowledge and behavior.